2020
DOI: 10.1111/jvim.15930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between a flash glucose monitoring system and a portable blood glucose meter for monitoring dogs with diabetes mellitus

Abstract: Background: Flash glucose monitoring system (FGMS; FreeStyle Libre) was recently validated for use in diabetic dogs (DD). It is not known if this system is clinically useful in monitoring DD. Objective: To compare the clinical utility of FGMS against blood glucose curves (BGCs) obtained with a portable blood glucose meter (PBGM) in monitoring DD. Animals: Twenty dogs with diabetes mellitus. Methods: Prospective study. Dogs with diabetes mellitus on insulin treatment for at least 1 month were included. Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 53 publications
2
42
0
1
Order By: Relevance
“…31 In diabetic dogs, a recent study showed that use of FGMS allowed better identification of BG nadirs and hypoglycemic episodes compared to the use of a PBGM. 32 The FGMS also allows the assessment of BG variations during consecutive days, enabling the clinician to make a more informed decision about the appropriate insulin dose, taking into account day-to-day variations in glycemic control. 32 Although the sensor might not remain on the cat for the full 14 days, using a simple application method, in most cats data can be obtained over a few days and nights.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 In diabetic dogs, a recent study showed that use of FGMS allowed better identification of BG nadirs and hypoglycemic episodes compared to the use of a PBGM. 32 The FGMS also allows the assessment of BG variations during consecutive days, enabling the clinician to make a more informed decision about the appropriate insulin dose, taking into account day-to-day variations in glycemic control. 32 Although the sensor might not remain on the cat for the full 14 days, using a simple application method, in most cats data can be obtained over a few days and nights.…”
Section: Discussionmentioning
confidence: 99%
“…32 The FGMS also allows the assessment of BG variations during consecutive days, enabling the clinician to make a more informed decision about the appropriate insulin dose, taking into account day-to-day variations in glycemic control. 32 Although the sensor might not remain on the cat for the full 14 days, using a simple application method, in most cats data can be obtained over a few days and nights. Additional studies are needed to investigate whether long-term use of FGMS during follow-up examination improves glycemic control in diabetic cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FGMS has been validated in dogs with DM treated on an outpatient basis as well as in dogs hospitalized for diabetic ketoacidosis. 18 , 19 , 20 , 21 , 22 One study also has validated the FGMS in hospitalized diabetic cats. 23 In this study, the investigators used 8 sutures to attach the sensor to mostly nonsedated cats, a technique that could be unacceptable to some veterinarians and owners.…”
Section: Introductionmentioning
confidence: 99%
“…A newer flash glucose monitoring system (FGMS; FreeStyle Libre, Abbott, Alameda, California) is appealing for use in cats because of its small size, ease of use, affordability, intuitive computer software, and factory calibration which eliminates the need for venipuncture and calibration with blood glucose concentration. The FGMS has been validated in dogs with DM treated on an outpatient basis as well as in dogs hospitalized for diabetic ketoacidosis 18‐22 . One study also has validated the FGMS in hospitalized diabetic cats 23 .…”
Section: Introductionmentioning
confidence: 99%